Tìm x sao cho: x2 (x - 3) / x - 9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (x - 140) : 7 = 33 - 23 . 3
(x - 140) : 7 = 27 - 8 . 3 = 27 - 24 = 3
x - 140 = 3 x 7 = 21
x = 21 + 140 = 161
b) x3 . x2 = 28 : 23
x5 = 25
=> x = 2
c) (x + 2) . ( x - 4) = 0
x = -2 hoặc 4
d) 3x-3 - 32 = 2 . 32 =
3x-3 - 9 = 2 . 9 = 18
3x-3 = 18 + 9 = 27
3x-3 = 33
=> x - 3 = 3
x = 3 + 3 = 6
b)
\(x^2=16\)
\(=>x^2=4^2\) hoặc \(x^2=\left(-4\right)^2\)
Vậy x = 4 hoặc x = -4
c) Kiểm tra lại nha
d)
\(\left(x-2\right)^5-32=0\)
\(=>\left(x-2\right)^5=0+32\)
\(=>\left(x-2\right)^5=32\)
\(=>\left(x-2\right)^5=2^5\)
\(=>x-2=2\)
\(=>x=2+2\)
\(=>x=4\)
a: Ta có: \(\left(x-3\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2+3x^2=-33\)
\(\Leftrightarrow x^3-9x^2+27x-27-x^3+27+6x^2+12x+1+3x^2=-33\)
\(\Leftrightarrow39x=-34\)
hay \(x=-\dfrac{34}{39}\)
b: Ta có: \(\left(x-3\right)\left(x^2+3x+9\right)-x\left(x-2\right)\left(x+2\right)=1\)
\(\Leftrightarrow x^3-27-x^3+4x=1\)
\(\Leftrightarrow4x=28\)
hay x=7
c: Ta có: \(\left(x+2\right)\left(x^2-2x+4\right)-x\left(x-3\right)\left(x+3\right)=26\)
\(\Leftrightarrow x^3+8-x^3+9x=26\)
\(\Leftrightarrow x=2\)
`a) x(x + 5)(x – 5) – (x + 2)(x^2 – 2x + 4) = 3`
`<=>x(x^2-25)-(x^3-8)=3`
`<=>x^3-25x-x^3+8=3`
`<=>-25x=-5`
`<=>x=1/5`
`b) (x – 3)^3 – (x – 3)(x^2 + 3x + 9) + 9(x + 1)^2 = 15`
`<=>x^3-9x^2+27x-27-(x^3-27)+9(x^2+2x+1)=15`
`<=>-9x^2+27x+9x^2+18x+9=15`
`<=>45x+9=15`
`<=>45x=6`
`<=>x=6/45=2/15`
`c) (x+5)(x^2 –5x +25) – (x – 7) = x^3`
`<=>x^3-125-x+7=x^3`
`<=>x^3-x-118=x^3`
`<=>-x-118=0`
`<=>-x=118<=>x=-118`
`d) (x+2)(x^2 – 2x + 4) – x(x^2 + 2) = 4 `
`<=>x^3+8-x^3-2x=4`
`<=>8-2x=4`
`<=>2x=4<=>x=2`
1) A = \(\dfrac{2x-1}{x+3}\) = \(\dfrac{3}{2}\) (=) (2x-1).2 = 3.(x+3)
(=) 4x-2 =3x+9
(=) 4x-3x = 9+2
(=) x = 11 (tm)
2) Để \(\dfrac{A}{B}\)< \(^{x^2}\)+5 (=) \(\dfrac{2x-1}{x+3}\): \(\dfrac{2}{x^2-9}\) < \(x^2\)+5
(=) \(\dfrac{\left(2x-1\right)}{\left(x+3\right)}.\dfrac{\left(x-3\right)\left(x+3\right)}{2}\) < \(x^2\)+5
(=) \(\dfrac{\left(2x-1\right).\left(x-3\right)}{2}< x^2+5\)
(=) \(\dfrac{2x^2-6x-x+3}{2}\) < \(x^2\) +5
(=) \(2x^2\)- 7x + 3 < \(2x^2\)+ 10
(=) (\(2x^2\)-\(2x^2\)) - 7x < -3 +10
(=) -7x < 7
(=) x > -1